Bantuan makanan di Malaysia: Kajian daripada perspektif ekonomi Islam / Norzuraida Hasan - Norzuraida , Hasan (2018)
Poverty is one of the key factors that contributes to hunger and food insecurity, especially for the urban poor. Hence, food aid exists as a mechanism to help the poor and the less fortunate. Food aid refers to a set of instrument that is used to overcome the food supply problem among the less fortunate people. This instrument may come in the form of food aids, vouchers, and cash transfers. Some of the concepts of food aids are the soup kitchen, food stamp, food bank, food pantry, and suspended meal, whereby their main resource is donations. When viewed from the Islamic perspectives, several food distribution mechanisms are being promoted to ensure that these groups of less fortunate people would be able to get enough food supplies. These mechanisms include compulsory obligations and non-compulsory obligations, such as zakah, waqaf, charity, qurban, aqiqah, kiffarah, dam, and fidyah. In Malaysia, a number of food aid programs are provided for by the government and NGOs to help these people. This study was conducted to investigate the food aid program, which is funded by the government and the NGOs for urban poor people. It also aimed to identify the socio-economic conditions and factors that could have caused them to be dependent upon food aids. This study was conducted using the documentation method, observations, and interviews. Interviews were conducted with the authorities, the local government, NGOs, food aid receivers, and the religious experts. The collected data were analysed using content analysis via editing, triangulation, and comparisons. The results showed that the government and the NGOs have their own food aid programs and together, they play a big part in helping the urban poor receive food aids and increase their level of food security. It is hoped that this study could contribute to the efforts put forth by the government and to the existing implementing parties for their food aid programs. The findings in this study could be used as guidelines in their effort to improve and to strengthen the food aid management, so that it will be more effective towards serving the society and the Malaysian economy.